CIRCUMFERENTIAL BIOINSPIRED RIBLETS IN INTERNAL PIPE FLOW - Santos, Christian; Santos de Souza, Vanio Vicente; Lima Borges, Marcelo (Revista e-TECH: Tecnologias para Competitividade Industrial - ISSN - 1983-1838, 2025)
This work analyzes the influence of bioinspired riblets spaced 200 mm apart on the pressure drop behavior in pipeline flow. The riblets used are of triangular and semicircular geometry, manufactured using a 3D filament printer and applied to the inner surface of a PVC pipeline. The experiment was conducted on a closed-loop test bench, with pressure and flow sensors, and an Arduino for data acquisition. The results indicated that triangular riblets reduced the pressure drop by up to 10.35% for flow rates of 14 L/min, while semicircular riblets showed a significant increase in pressure drop for flow rates above 8 L/min. The semicircular riblets interact with vortices in the subviscous layers, increasing momentum exchange, and do not accumulate stresses at their tips, which contributes to the increase in pressure drop. Despite promising results, the true efficiency of riblets is still unknown and limited, due to factors such as manufacturing difficulty, applicability, and geometry that is yet to be optimized.